Prognostic and Predictive Value of CpG Island Methylator Phenotype in Patients with Locally Advanced Nonmetastatic Sporadic Colorectal Cancer - Yuwei Wang; Yadong Long; Ye Xu; Zuqing Guan; Peng Lian; Junjie Peng; Sanjun Cai; Guoxiang Cai (Gastroenterology Research and Practice)
Purpose. In the present study, the prognostic significance of CpG island methylator phenotype (CIMP) in stage II/III sporadic colorectal cancer was evaluated using a five-gene panel. Methods. Fifty stage II/III colorectal cancer patients who received radical resection were included in this study. Promoter methylation of p14ARF, hMLH1, p16INK4a, MGMT, and MINT1 was determined by methylation specific polymerase chain reaction (MSP). CIMP positive was defined as hypermethylation of three or more of the five genes. Impact factors on disease-free survival (DFS) and overall survival (OS) were analyzed using Kaplan-Meier method (log-rank test) and adjusted Cox proportional hazards model. Results. Twenty-four percent (12/50) of patients were characterized as CIMP positive. Univariate analysis showed stage III (P=0.049) and CIMP positive (P=0.014) patients who had significantly inferior DFS. In Cox regression analysis, CIMP positive epigenotype was independently related with poor DFS with HR = 2.935 and 95% CI: 1.193–7.220 (P=0.019). In patients with CIMP positive tumor, those receiving adjuvant chemotherapy had a poor DFS than those without adjuvant chemotherapy (P=0.023). Conclusions. CIMP positive was significantly correlated with decreased DFS in stage II/III colorectal cancer. Patients with CIMP positive locally advanced sporadic colorectal cancers may not benefit from 5-fluorouracil based adjuvant chemotherapy.